Bridging Extraction Metrics and Sensory Perception: A Single-Origin Rwandan Red Bourbon Pour-Over Case Study Using TDS Profiling - Afif, Fuadi; Damasdino, Fian; Fithriya, Dwi Nur Laela; Hermawan, Hary (Gastronomy and Culinary Art, 2025)
This study investigates the relationship between instrumental extraction metrics and perceived sensory outcomes in a controlled pour-over brewing session using single-origin Rwandan Red Bourbon coffee. The brewing parameters were carefully standardized, with a coffee dose of 10 grams, 180.5 grams of water at 90°C, and a medium grind size of 960 μm. The total brew time was 2 minutes and 31 seconds, resulting in a Total Dissolved Solids (TDS) value of 2.07%, measured using a DiFluid R2 Extract refractometer. While this TDS value indicates a quantitatively optimal extraction near the upper limit of Specialty Coffee Association standards, the perceived flavor was reported as neutral and weak, lacking distinctive bitterness, acidity, or sweetness. This discrepancy highlights the influence of post-roast aging (125.2 days) and the absence of trained sensory calibration on flavor perception. The findings demonstrate a measurable disconnect between digital extraction metrics and subjective sensory quality, emphasizing the limitations of using TDS as a standalone quality indicator. This study underscores the importance of integrating quantitative analysis with sensory protocols, especially for non-professional brewers, and contributes to a growing body of data-driven approaches in the field of specialty coffee evaluation. It also opens a path toward reproducible brewing science accessible outside traditional laboratory or cupping environments.